Mechanisms of change in multicomponent group-based treatment for patients suffering from medically unexplained physical symptoms - Řiháček, Tomáš; Čevelíček, Michal; Boehnke, Jan R; Pourová, Martina; Roubal, Jan (Psychotherapy research, 2022)
Understanding psychological mechanisms of change is essential to advance treatments for patients suffering from medically unexplained physical symptoms (MUPS). This study aimed to test the role of selected change mechanisms (incl. interoceptive awareness, emotional regulation skills, symptom acceptance, relational needs satisfaction, clarification of meaning, working alliance, and group cohesion) in the modification of patients' somatic symptom intensity and well-being. N = 290 patients suffering from MUPS participated in a multi-component group-based treatment at seven clinical sites. Data were collected weekly. Multi-level modeling was used to test cross-lagged relationships between the hypothesized mechanisms and outcomes in terms of Granger causality (with lags of 1, 2, and 3 weeks). None of the mechanisms predicted a time-lagged change in outcomes in the expected direction. In fact, there was a consistent pattern of negative time-lagged relationships (i.e., an increase in a mechanism predicted worsening of the outcome). Findings consistent with the hypothesized role of the mechanisms were found only in concurrent relationships between mechanisms and outcomes. This study did not support time-lagged relationships under the condition of weekly measurement and many methodological factors remain to be considered (e.g., a finer time resolution).
Keywords: Psychology; multicomponent treatment; change mechanisms; pacienti bez organického nálezu; lidé; group psychotherapy; psychologie; skupinová psychoterapie; Medically Unexplained Symptoms; Psychotherapy, Group; medically unexplained physical symptoms; Treatment Outcome; výsledek terapie; Humans